2019
DOI: 10.3390/met9080859
|View full text |Cite
|
Sign up to set email alerts
|

Research on Four-Point Air Bending Process and Contour Detection Method for JCO Forming Process of LSAW Pipes

Abstract: Aiming at the forming efficiency and roundness of the longitudinal submerged arc welded (LSAW) pipes in JCO (J-shape to C-shape to O-shape) forming process, this paper proposes a four-point air bending process. Compared with the traditional three-point air bending process, The new process can provide a more uniform bending moment, does not need to crimp the edges of steel sheet, shorten the residual straight segment length, and lengthen the forming length in single pass. The mechanical model is established to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The advantages of the new technology include fewer steps to the formation, higher productivity, dispensing with crimping process, less residual stress, higher flexibility, better forming quality, and preventing the expansion of flaws. Zhang et al 22 established the mechanical model of the four-point bending JCOC process by analyzing the static equilibrium conditions and elastic–plastic deformation, simulated the process to find the maximum punch spacing, and further determined the formulation principles of other process parameters. In addition, a contour detection method for the LSAW pipes in forming process is proposed based on machine vision.…”
Section: Jco Manufacturing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the new technology include fewer steps to the formation, higher productivity, dispensing with crimping process, less residual stress, higher flexibility, better forming quality, and preventing the expansion of flaws. Zhang et al 22 established the mechanical model of the four-point bending JCOC process by analyzing the static equilibrium conditions and elastic–plastic deformation, simulated the process to find the maximum punch spacing, and further determined the formulation principles of other process parameters. In addition, a contour detection method for the LSAW pipes in forming process is proposed based on machine vision.…”
Section: Jco Manufacturing Processmentioning
confidence: 99%
“…The advantages of the new technology include fewer steps to the formation, higher productivity, dispensing with crimping process, less residual stress, higher flexibility, better forming quality, and preventing the expansion of flaws. Zhang et al 22 established the mechanical Figure 8. Principle of the intelligent control system for forming steel pipe with JCO process.…”
Section: Jco Formingmentioning
confidence: 99%
“…An analysis of the existing methods and means for determining the degradation of the mechanical properties of materials during the operation of structures in real time showed that they are all intended for the study of one type of deformation: tension [ 37 , 38 , 39 ] or bending [ 40 , 41 , 42 , 43 ], while under real conditions loading forces act on the material, under combined conditions of deformation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Relative Workmentioning
confidence: 99%
“…The current main manufacturing processes of submarine pipeline include UOE [1][2][3] and JCO [4,5]. In order to meet the ovality standard [6], a calibration process is needed after forming, mostly an expanding process.…”
Section: Introductionmentioning
confidence: 99%